2007
DOI: 10.1063/1.2768861
|View full text |Cite
|
Sign up to set email alerts
|

Coupling nanowire chemiresistors with MEMS microhotplate gas sensing platforms

Abstract: Recent advances in nanotechnology have yielded materials and structures that offer great potential for improving the sensitivity, selectivity, stability, and speed of next-generation chemical gas sensors. To fabricate practical devices, the "bottom-up" approach of producing nanoscale sensing elements must be integrated with the "top-down" methodology currently dominating microtechnology. In this letter, the authors illustrate this approach by coupling a single-crystal SnO 2 nanowire sensing element with a micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
53
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(58 citation statements)
references
References 26 publications
5
53
0
Order By: Relevance
“…In our case, the α value is higher than the obtained with individual SnO 2 nanowires with diameter about 100 nm obtained following an equivalent procedure (α ≈ 0.07) [17]. SnO 2 devices fabricated with alternative methodologies showed different α values highlighting the strong influence in this parameter of changes in the device processing [33].…”
Section: Resultsmentioning
confidence: 44%
See 2 more Smart Citations
“…In our case, the α value is higher than the obtained with individual SnO 2 nanowires with diameter about 100 nm obtained following an equivalent procedure (α ≈ 0.07) [17]. SnO 2 devices fabricated with alternative methodologies showed different α values highlighting the strong influence in this parameter of changes in the device processing [33].…”
Section: Resultsmentioning
confidence: 44%
“…Previous works on individual SnO 2 nanowires demonstrated that the relationship given in eq.9 is followed by very similar device configurations and gas measurements [33]. In practise, α is a parameter dependent on the experimental conditions and the intrinsic properties of the metal oxide, such as the material quality and the diameter in the case of nanowires [28][29][30].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was established that Joule self-heating of NWs operated under a passing electric current can be applied for NW-based gas sensors. Meier et al ( 2007a, b ) and Hernandez-Ramirez et al ( 2007a, b ) have shown that sensors based on individual NWs with selfheating can be fabricated with power consumption of only a few tens of microwatts, much less than that required for thin-fi lm sensors mounted on microhotplates, which usually require milliwatts to work in continuous mode. Moreover, Prades et al ( 2008 ) have demonstrated that the response of the sensors to 0.5 ppm NO 2 without a heater ( I m = 10 nA) was the absolute equivalent to that with a heater ( T = 175 °C) (see Fig.…”
mentioning
confidence: 98%
“…(2) Among various sensor materials, SnO 2 is an ideal and important material for semiconductor-type gas sensors. (3) Therefore, various types of nanostructured SnO 2 such as nanoparticles, (4) nanowires, (4,6,7) nanobelts (4) and nanorods (4,8) have been prepared as gas-sensor materials by a general sol-gel technique, (9,10) a hydrothermal or solvothermal method, (9) or some physical vapor deposition methods (11,12) because they have provided a promising way towards miniaturized ultrasensitive gas sensors. (9) Recently, mesoporous SnO 2 (m-SnO 2 ) powder has also been prepared by employing the self-assembly of n-cetylpyridinium chroride as a template and Na 2 SnO 3 as a tin source, and thermal stabilizing by a treatment in an aqueous phosphoric acid solution.…”
Section: Introductionmentioning
confidence: 99%